Structurally characterized normal and abnormal N-heterocyclic carbene based palladium and gold complexes and their catalysis - Xu, Xiangya (2011)
N-heterocyclic carbenes (NHCs) have been extensively investigated and widely used as more efficient ligands. The experimental and theoretical evidences showed that C4 or C5-bound NHCs (aNHCs) are stronger donor ligands than C2-bound NHCs (nNHCs). It is expected that the outstanding strong donor abilities of aNHCs have a great influence on catalysis. However the synthesis and catalytic activity of M-aNHC complexes have not been thoroughly investigated till now compared to those of M-nNHC complexes. The objectives of this thesis were to investigate that the aNHCs ligands in catalysis either using in situ generation system or well-defined M-aNHC complexes.